ALBANIAN ACCOUNTING TRENDS IN ACCORDANCE WITH EU STANDARDS - Kaduku, Ilir (European Scientific Journal, ESJ, 2012)
A lot of work has gone to standardize the financial accounts of insurance and requirements of reimbursement ability. These projects are made by various international organizations. This will alter the way the insurance companies keep their accounts and how they design strategies. All this work in accounting is being done to increase transparency and provide the most realistic accounts of insurance. This is an indirect form to protect the policyholders. Even the regulation on repayment ability is a method of protecting policyholders. Accounting is the process of collecting and reporting financial information about entity or about a group of units. Accounting practices are developed over time and they reflect the traditional national accounts. With the development of EU and increased activity of insurance companies or other companies outside the national borders, finding of a common way to present financial data of companies is becoming more critical. In connection with commercial enterprises, accounting information users include managers, investors, potential investors, lenders, investment analysts, regulators and consumers. The accounting changes outlined here, will be mandatory for insurance companies listed on stock exchange. However it is expected that other companies will adopt these rules as they aim to clearly present the true situation of the company, critical for managing a company.